2005
DOI: 10.1253/circj.69.1361
|View full text |Cite
|
Sign up to set email alerts
|

Monophasic Action Potential Duration at the Crista Terminalis in Patients With Sinus Node Disease

Abstract: inus arrest and sinoatrial block (sinus node disease: SND) decrease cardiac output and elicit AdamStokes syndrome. To improve the activities of daily life of patients with SND, pacemaker therapy is used, but because the incidence of SND increases with age, the number of the patients and cost of pacemaker therapy are increasing in developed countries.SND occurs because of either a decrease in the pacemaker potential to a level below the threshold of overshoot of the action potential or exit block of the pacemak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…The resting membrane potential (RMP), maximum upstroke velocity (dV/dt max ), action potential amplitude (APA), and action potential duration at 90% repolarization (APD 90 ) were measured as −75.2 mV, 160 mV/ms, 110 mV, and 312 ms, respectively. These parameters were consistent with previous models developed by Grandi et al [33], Courtemanche et al [43], and Nygren et al [44], and APD 90 was within the scope of previously reported experimental data [45][46][47][48], as listed in Table 1.…”
Section: Electrophysiological Properties Of a Single Atrialsupporting
confidence: 92%
“…The resting membrane potential (RMP), maximum upstroke velocity (dV/dt max ), action potential amplitude (APA), and action potential duration at 90% repolarization (APD 90 ) were measured as −75.2 mV, 160 mV/ms, 110 mV, and 312 ms, respectively. These parameters were consistent with previous models developed by Grandi et al [33], Courtemanche et al [43], and Nygren et al [44], and APD 90 was within the scope of previously reported experimental data [45][46][47][48], as listed in Table 1.…”
Section: Electrophysiological Properties Of a Single Atrialsupporting
confidence: 92%
“…Note that the RAA model was validated using experimental data from human (APD 90 in the model is 230 ms at a BCL of 1000 ms, compared to 255 ± 45 ms observed by Bosch et al . (1999)) and other models were validated by their APD relative to the RAA using either human or canine data (as necessitated by human data availability or lack thereof; Feng et al 1998; Li et al 2001; Burashnikov et al 2004; Katoh et al 2005; Gong et al 2008). Additional details of the AP morphology validation are presented in the Online Supplement (Figs S8–S12).…”
Section: Resultsmentioning
confidence: 99%
“…The absence of particular experimental data sets is a common limitation of modelling studies accounting for regional heterogeneity in the human atria, and, in common with the present investigation, the approach of incorporating data from alternative species has been implemented in previous studies (Courtemanche et al 1998; Seemann et al 2006; Aslanidi et al 2011 b ; Dorn et al 2012). It is encouraging that such an approach has resulted in models that can replicate regional APD and AP morphology differences observed in both the human and the canine atria (Feng et al 1998; Burashnikov et al 2004; Katoh et al 2005; Gong et al 2008). It should be noted that major results of the present study were confirmed by replacing the updated CRN‐based models with a different family of human atrial AP models developed recently by Dorn et al (2012).…”
Section: Discussionmentioning
confidence: 99%
“…Baba et al, 15 who compared 90 SSS patients and 14 healthy subjects, found that the high right atrium (HRA) -HBE interval and HRA -coronary sinus interval were significantly prolonged in the SSS group, and Katoh et al 16 reported that the monophasic action potential duration at the crista terminalis in the SSS group (n=13) was significantly prolonged compared with the control group (n=13). Both studies described a significant disturbance of intraatrial conduction in patients with SSS.…”
Section: Evaluation Of Intra-atrial Conductionmentioning
confidence: 99%